Central and Extrapontine Myelinolysis Affecting the Brain and Spinal Cord. An Unusual Presentation of Pancreatic Encephalopathy - Biller, Jose; Hornik, Alejandro; Rodriguez-Porcel, Federico; Agha, Caroline; Flaster, Murray; Morales Vidal, Sarkis Gibran; Schneck, Michael J.; Lee, John (Frontiers in Neurology, 2012)
Abstract: Pancreatic encephalopathy refers to a gamut of neuropsychiatric symptoms complicating acute pancreatitis. Osmotic myelinolisis is a known complication of pancreatic encephalopathy. We evaluated a 58 year old woman with pancreatic encephalopathy associated to pontine and extrapontine myelinolisis involving the brain and spinal cord. To our knowledge, this is the first clinic pathological case report of pancreatic encephalopathy involving the spinal cord.